AYA22A Aptamers Mitigate Peanut Allergenicity: Insights from Degranulation Assays and Modulating Immune Responses - Mohamad Ammar Ayass; Trivendra Tripathi; Natalya Griko; Ramya Ramankutty Nair; Tutku Okyay; Jin Zhang; Kevin Zhu; Kristen Melendez; Victor Pashkov; Lina Abi-Mosleh (Allergies)
Food allergy, particularly peanut allergy (PA), is a growing health concern affecting millions globally. PA can lead to severe reactions, including fatal anaphylaxis. Despite the availability of FDA-approved therapies like Palforzia, a cure remains elusive. Current immunotherapies show promise but lack a definitive cure. This study applies an established computational biology tool to design aptamers targeting Ara h1 and Ara h2. The in silico design aims to streamline the selection process, enabling cost-effective and rapid identification of aptamer candidates. The developed aptamers (AYA22A, including AYA22AR321, AYA22AR211, and AYA22AR524), demonstrated efficacy in inhibiting degranulation of RBL-2H3 cells (rat basophilic leukemia cell line) in vitro. They showed promise in neutralizing peanut allergen-induced immune responses. The selected aptamers inhibited degranulation in RBL-2H3 cells, addressing concerns in raw peanuts. Moreover, these aptamers demonstrated stability and effectiveness in peanut plant seeds and commercial products. Our aptamers exhibited potential in modulating immune responses associated with peanut allergy. They influenced Th1/Th2 balance, indicating a role in cytokine regulation. In vitro studies also showed the aptamers’ impact on immune cell expression and cytokine production, resembling responses observed with established immunotherapies. The findings suggest AYA22A aptamers as a potential therapeutic option for peanut allergy, providing a basis for further in vivo investigations.